(untitled) (Research, Society and Development, 2021)
The CRISPR-Cas9 technique has been widely studied lately and has become a revolutionary tool in the field of genetics, especially in editions and therapies. This is a defense mechanism found in bacteria that cleaves a specific piece of DNA from the bacteriophage and aggregates it into the bacteria’s own DNA. By studying the behavior and effectiveness of this technique in bacteria, scientists carried out studies for use in the laboratory and found that it could be used for gene editing in a general, more accurate and cheaper way. The biggest challenge in using CRISPR-Cas9 lies in the practicality of the technique in human beings, since there is a risk of misuse for selfish purposes that could bring a huge imbalance in society. The objective of this work is to point out the positive progress of gene therapy and the positive impact of a new innovative technique capable of bringing great benefits due to its simplicity in working on a large scale of genomes, facilitating the prevention of innate or acquired genetic diseases. A bibliographic survey of articles from up to 05 years ago was carried out on research platforms, both in English and in Portuguese. It was then concluded that gene therapy brings enormous benefits to society in general if used legally approved, regulated and monitored, aiming at the well-being and health of populations.